Identification of U937JAK3-M511I Acute Myeloid Leukemia Cells as a Sensitive Model to JAK3 Inhibitor - Si, Hongfei; Wang, Jie; He, Rui; Yu, Xiuwen; Li, Shan; Huang, Jing; Li, Jie; Tang, Xia; Song, Xiaojuan; Tu, Zhengchao; Zhang, Zhang; Ding, Ke (Frontiers in Oncology, 2022)
Mutated JAK3 has been considered a promising target for cancer therapy. Activating mutations of JAK3 are observed in 3.9-10% of AML patients but it is unclear whether AML cells are sensitive to JAK3 inhibitors and no disease-related human AML cell model has been reported. We have identified U937 as the first human AML cell line expressing the JAK3M511I activated mutation, and confirmed that JAK3 inhibitors sensitively suppress proliferation of U937 AML Cells.